Contribuição para uso da goma de cajueiro como um insumo industrial - Souza, Arthur Claudio Rodrigues de (2014)
Gums are widely used in industrial processes. The gums are high molecular weight polymers and may be derived from algae, seeds, animals or microorganisms. The food industry makes use of these polymers to assign some of their products for their best quality characteristics through changes and control of viscosity, stability, texture, durability and consistency. The cashew tree gum is presented as a possible substitute for gum arabic and studies have brought very promising results. However there is no study or methodology for large scale production of cashew tree gum. All methods are described for laboratory scale. This paper aims to bring contributions to large-scale production of cashew tree gum and reviews the composition and relevant properties of the gum which can be affected by heat treatments during the manufacturing process. Therefore, this study was the evaluation of parameters for continuous and automated production of cashew tree gum, which presented the step of solubility and separation of insoluble part as the main obstacle in the process. Furthermore, the gum was purified and subjected to heat treatment compared to the purified gum without heat treatment so as to observe possible structural changes due to production or industrial uses of cashew tree gum. The results showed the gum stability under the test conditions. The composition of cashew gum is similar to gum arabic. A 5% solution shows shear thinning behavior and Newtonian plateau at 3.3 mPa.s The cashew gum has high levels of arabinose and glucuronic acid and low levels of galactose when compared to values reported in the literature for cashew gum from Braz